Addressing the Data Location Assurance Problem of Cloud Storage Environments - Noman, Ali (Université d'Ottawa / University of Ottawa, 2018)
In a cloud storage environment, providing geo-location assurance of data to a cloud user is very challenging as the cloud storage provider physically controls the data and it would be challenging for the user to detect if the data is stored in different datacenters/storage servers other than the one where it is supposed to be. We name this problem as the “Data Location Assurance Problem” of a Cloud Storage Environment. Aside from the privacy and security concerns, the lack of geo-location assurance of cloud data involved in the cloud storage has been identified as one of the main reasons why organizations that deal with sensitive data (e.g., financial data, health-related data, and data related to Personally Identifiable Infor-mation, PII) cannot adopt a cloud storage solution even if they might wish to. It might seem that cryptographic techniques such as Proof of Data Possession (PDP) can be a solution for this problem; however, we show that those cryptographic techniques alone cannot solve that. In this thesis, we address the data location assurance (DLA) problem of the cloud storage environment which includes but is not limited to investigating the necessity for a good data location assurance solution as well as challenges involved in providing this kind of solution; we then come up with efficient solutions for the DLA problem. Note that, for the totally dis-honest cloud storage server attack model, it may be impossible to offer a solution for the DLA problem. So the main objective of this thesis is to come up with solutions for the DLA problem for different system and attack models (from less adversarial system and attack models to more adversarial ones) available in existing cloud storage environments so that it can meet the need for cloud storage applications that exist today.
Keywords: cloud storage security; data location assurance for cloud; cloud computing security; DLAS; proof of data possession solution for cloud; cloud computing